Parasite communities associated with the Cape gurnard (Chelidonichthys capensis) and the lesser gurnard (C. queketti) from South Africa - Mackintosh, Amy Leigh (Department of Biological Sciences, 2020)
The Cape gurnard (Chelidonichthys capensis) and the lesser gurnard (Chelidonichthys queketti) are two members of the Triglidae family found off Southern Africa. Chelidonichthys capensis is distributed from depths of 10 m to 390 m in subtropical waters between Namibia and Mozambique, while C. queketti is distributed from 0 m to 150 m in subtropical waters from Namibia to southern Mozambique. Little is known about the biology, ecology and life cycles of these two species. Additionally, the parasite community of these two gurnards has not yet been surveyed, although there are records of a number of copepods infecting both species that have been documented for taxonomic purposes. This study aims to examine the macroparasite assemblages of both gurnard species from the west and south coasts of South Africa and determine whether the parasite communities show significant intra-specific, special differences or inter-specific differences. A total of 70 Chelidonichthys capensis and 87 C. queketti were examined, with a total of 13 parasitic taxa found infecting C. capensis, ten of which are new host records, while 15 parasitic taxa were found infecting C. queketti, 13 of which are new host records and one of which is a new geographic record. The nematode Anisakis pegreffii was the most prevalent parasite infecting C. capensis (75.7%), and an unidentified cyst was the most prevalent parasite infecting C. queketti (69%). Parasites recorded to infect both gurnard species include the cestode Tentacularia coryphaenae, the acanthocephalan Corynosoma australe, and the copepods Lernentoma asellina and Medesicaste penetrans. A Caligus species was only recorded to infect C. capensis and the unidentified cyst was only recorded infecting C. queketti. This study was also able to identify two biological tag species for potential use in population structure studies of both gurnards, namely A. pegreffii and T. coryphaenae, based on significant regional differences in prevalence and infection intensity levels. In comparison to other Chelidonichthys species, C. capensis has the second highest and C. queketti has the third highest number of recorded parasite taxa, with C. lucerna having the highest number (22 species) of parasites recorded. The new host records for C. capensis and C. queketti, and the new geographic record, contribute to our knowledge of these demersal fish species and of marine biodiversity in South Africa.